Perancangan Sistem Kesehatan dan Keselamatan Kerja (SMK3) di PT. SPINDO 1 - Andy William; Togar W.S. Panjaitan (Jurnal Titra, 2014)
PT. SPINDO unit 1 is one of the big and famous company which produces steel pipe. Nowadays, PT. SPINDO 1 is willing to design health and management system (SMK 3) because of the high rate of the workplace accident for the year of 2013 that is 93 cases. Besides that, government rules stated that every company shall ensure the health and work safety of their employees within the scope of company or working area.The health and management system (SMK 3) design by PT. SPINDO appropriates with the actual conditions of the company and covers the HIRARC documents. Finally the result of the SMK 3 reached 62.69% which can be said “Good” according to the Government Regulation (PP) no 50 of 2012.